Restructuring Electronic Traffic Violation Enforcement Regulations to Achieve Justice - Arpan; Ruslina Dwi Wahyuni (Yayasan Azhar Amanaa Yogyakarta, 2025)
The implementation of Electronic Traffic Law Enforcement (ETLE) represents a form of modernization in traffic law enforcement aimed at enhancing the effectiveness, transparency, and accountability of traffic and road transport violation handling. Normatively, the use of electronic devices in traffic law enforcement has obtained a legal basis under Article 272 of Law Number 22 of 2009 on Road Traffic and Transportation. However, in practice, the implementation of ETLE reveals a number of fundamental issues related to regulatory inconsistency, normative gaps, and the insufficient internalization of substantive justice values within this technology-based law enforcement system. This study aims to analyze the reasons why regulations governing electronic traffic and road transport law enforcement have not yet been grounded in justice-based values, to identify normative, institutional, and procedural weaknesses in the implementation of ETLE, and to formulate a reconstruction of electronic traffic law enforcement regulations oriented toward justice values. This research employs a doctrinal legal research method with a socio-legal approach, adopts a constructivist paradigm, and is supported by primary data obtained through interviews and field observations. The analysis is conducted using Pancasila justice theory as the grand theory, legal effectiveness theory as the middle-range theory, and progressive legal theory as the applied theory. The findings indicate that the current ETLE system prioritizes administrative certainty and technical efficiency over substantive justice. The main weaknesses lie in the hierarchical inconsistency of regulations, deviations from the principle of personal liability, the implicit reversal of the burden of proof, the absence of clear technical standards for electronic evidence, weak mechanisms for the protection of citizens’ rights, and institutional fragmentation accompanied by poor inter-agency coordination. These conditions give rise to structural injustice, particularly when vehicle owners are positioned as subjects of legal responsibility without due consideration of the actual perpetrators of traffic violations. Therefore, this study positions the reconstruction of ETLE regulations as a conceptual necessity to shift the paradigm of traffic law enforcement from administrative certainty toward substantive justice, through the clarification of legal responsibility subjects, the strengthening of citizens’ rights protection, and the integration of accountable and human-oriented technology governance.